Centralized Data Governance: The Key to Digital Transformation and Improving Accountability at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province - Arisal (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This article analyzes data governance issues at the Regional Office of the Ministry of Religious Affairs of West Sulawesi Province, resulting in slow public services and complex bureaucracy. Various structural and technical issues, such as the lack of information system integration that creates the phenomenon of